BUILDING AN INNOVATIVE MICRO-ENTERPRISE ECOSYSTEM THROUGH ENTREPRENEURSHIP EDUCATION, DIGITAL TRANSFORMATION, AND DATA LITERACY IN THE DIGITAL ECONOMY ERA - Sutrisno (Technopreneurship and Educational Development Review (TENDER), 2025)
This study aims to analyze how entrepreneurship education, digital transformation, and data literacy can synergistically contribute to building an innovative micro-enterprise ecosystem in the digital economy era. The research method used is a literature review with a qualitative approach and descriptive analysis. Data were obtained from scholarly articles retrieved through Google Scholar and various credible websites spanning 1983–2025. From an initial 50 articles, a strict selection process based on relevance and validity resulted in 37 articles used as the primary sources for analysis. The findings reveal that entrepreneurship education plays a role in shaping creative mindsets, innovative capabilities, and adaptive attitudes among micro-entrepreneurs in response to technological change. Digital transformation has been shown to enhance operational efficiency and expand market reach through the implementation of digital platforms and online marketing systems. Meanwhile, data literacy strengthens entrepreneurs’ analytical capabilities for making information-based decisions. The synergy of these three components creates a resilient, adaptive, and competitive micro-enterprise ecosystem amid the dynamics of the digital economy.